2019
DOI: 10.3389/fpls.2019.00647
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Invasiveness of Ludwigia and Nelumbo in Shallow Temperate Fluvial Lakes

Abstract: The relationship between invasive plant functional traits and their invasiveness is still the subject of scientific investigation, and the backgrounds of transition from non-native to invasive species in ecosystems are therefore poorly understood. Furthermore, our current knowledge on species invasiveness is heavily biased toward terrestrial species; we know much less about the influence of allochthonous plant traits on their invasiveness in aquatic ecosystems. In this paper, we present the results of a study … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 62 publications
0
13
1
Order By: Relevance
“…Bolpagni (2013aBolpagni ( , 2013b and Bolpagni et al (2017) found that Lagarosiphon major and Elodea nuttallii create extensive submerged meadows that almost completely replace native macrophyte communities belonging to N2000 habitats 3140 and 3150. Nelumbo nucifera and Ludwigia hexapetala seem to actively compete with native species (Bolpagni et al, 2014b;Villa et al, 2017Villa et al, , 2018Tóth et al, 2019) due to their enhanced competitive ability for limiting resources and their tolerance to edaphic conditions variability (Tóth et al, 2019). Some studies focused on the impact of Lemna minuta on freshwater ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Bolpagni (2013aBolpagni ( , 2013b and Bolpagni et al (2017) found that Lagarosiphon major and Elodea nuttallii create extensive submerged meadows that almost completely replace native macrophyte communities belonging to N2000 habitats 3140 and 3150. Nelumbo nucifera and Ludwigia hexapetala seem to actively compete with native species (Bolpagni et al, 2014b;Villa et al, 2017Villa et al, , 2018Tóth et al, 2019) due to their enhanced competitive ability for limiting resources and their tolerance to edaphic conditions variability (Tóth et al, 2019). Some studies focused on the impact of Lemna minuta on freshwater ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…The Superior, Middle and Inferior lakes are characterized by high turbidity and eutrophic conditions, and the water level is kept fixed to prevent flooding the city of Mantua. Macrophyte communities in the system are populated by both native ( T. natans, N. lutea , N. alba in open water areas, and P. australis in wetlands) and alien species [ 46 , 59 , 60 ]: Nelumbo nucifera Gaertn., introduced into the lake around a century ago, and Ludwigia hexapetala (Hook. & Arn.)…”
Section: Methodsmentioning
confidence: 99%
“…Leaf reflectance in the visible to shortwave infrared range (350–2500 nm, with a spectral resolution of 3 nm for wavelengths under 1000 nm, and < 8 nm up to 2500) was measured using a portable full range spectroradiometer (SR-3500, Spectral Evolution, Lawrence, USA), following the protocol described in Tóth et al [ 60 ]. After 20-min dark adaptation, leaves were laid on a flat neoprene plate (reflectance factor < 5%) to minimize background reflection of light transmitted through the leaves.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations